Friction deposition additive manufacturing of alloy 718: Effect of post-heat treatment on microstructures and mechanical properties - Santiagu C.J.D.; Ramachandran D.; Gangaraju M.K.; Sajja Rama K.R. (My University, 2025)
The friction deposition process is well known for surface repairs and depositing corrosion and wear resistant coatings. In this study, we explored friction deposition additive manufacturing (FDAM) for producing alloy 718 components. The microstructure evolution, temperature distribution during the process, and room temperature tensile properties of the FDAM processed alloy 718 were studied. Multi-layer deposits with sound metallurgical bonding at the layer interfaces were obtained. The deposits showed fine equiaxed grains with grain size varying from 4 to 7 μm across the deposit height, having finer grains (~4 μm) closer to the substrate and coarser grains (~7 μm) at the top of the deposit. Thermography analysis was employed to analyze the temperature distribution during friction deposition, revealing a maximum peak temperature of 1121°C on the deposited material. Subsequently, the material cooled rapidly at a rate of 30°C/s. The FDAM sample in the as-deposited condition exhibited higher tensile strength than the wrought alloy 718 in the solution-treated (ST) condition. The post-direct aging (DA) of the FDAM sample resulted in a 41% improvement in tensile strength than the as-deposited condition and met the tensile properties of wrought alloy 718 in aged condition as per aerospace material specifications (AMS). Furthermore, there were no significant variations observed in the tensile properties across different regions of the FDAM deposit height. Graphical abstract: [Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.